Conceptual Design for Synthesis of Benzaldehyde from Natural Cinnamomum Cassia Oil: Experiments and Simulation - Nguyen, Trung Dung; Phan, Ngoc Quang; Nguyen, Van Anh; Ta, Hong Duc; Meyer, Xuan-Mi; Blanco, Jean Francois; Cognet, Patrick; Meyer, Michel; Cao, Hong Ha (Vietnam Journal of Science and Technology, 2024)
The results on the synthesis of natural benzaldehyde from trans-cinnamaldehyde in natural cinnamon essential oil are presented in this study. The synthetic experiments were carried out to get the primary input parameters for design and simulation, including reaction and extraction steps. The conversion of trans-cinnamaldehyde to benzaldehyde were achieved the highest conversion rate of 33.5 %, and the initial quantity of ethyl acetate solvent was 3825 kg/h used the Aspen Plus® software. The optimal stage of extraction was six, and the optimal quantity of ethyl acetate solvent was 3695 kg/h. In the distillation stage, a two-column design was proposed. The first column was for ethyl acetate solvent removal, whereas the second one was used for purifying the target product (benzaldehyde). The operating conditions of the columns were optimized not only based on the vapor feed but also the equipment cost to minimize the investment budget. The optimal parameters for the first column (D-1) and the second column (D-2) were the number of theoretical plates of 7 (D-1), 11 (D-2); the feed position of 3 (D-1), 5 (D-2); the real reflux ratio of 0.11 (D-1), 2.59 (D-2); and the distillate for feed fraction of 0.9536 (D-1), 0.2171 (D-2), respectively.